The United Nations Global Compact: A CSR Milestone. (March 2013) - Post, James E.
The author focuses attention on some of the historical antecedents of the United Nations Global Compact. Developments such as the Global Compact do not arrive "whole cloth" but require people and institutions to be in a "state of readiness" for the idea. The article discusses Secretary-General Annan's challenge to action, the historical background of three stages of corporate social responsibility, and the future of global corporate responsibility.